Free oscillation of nonlinear elastic pipelines - Горбатов, В. С.; Першаков, В. М. (Proceedings of National Aviation University (archive), 2021)
The results of analytical resecerches of free oscillation of pipelines taking into account its geometrical nonlinearity and influence of own pipe's weight and liquid inside it are presrnted in this article. Considering of the nonlinearity of the pipeline allows to know forecast of dynamicol behaviour of energetic system more conectly.